Potiguara Indigenous Narratives: Oral Literature, Enchanted Beings, History, and Tradition - Barbosa, Milena Veríssimo (Revista Letras Raras, 2024)
The art of narrating, telling fabulous stories of great deeds, and describing supernatural beings and their actions are inherent tasks for individuals in various societies from ancient times to the present. Indigenous peoples, including the Potiguara, use storytelling through elders to communicate their culture, identity, and traditions. However, few published works gather the diversity of narratives shared through oral tradition. In this context, this work aims to analyze the narratives of the Mangrove Father and the Potiguara Witches, present in the collective imagination of the Potiguara people, located on the Northern Coast of Paraíba, to share narratives of the oral tradition that permeate the indigenous daily life of this region, in order to share narratives from the oral tradition that permeate the daily life of the indigenous people of this region, identifying common themes and structures, in comparison with other myths and stories inherited from other cultures.. Authors such as Cascudo (2007), Munduruku (2009), Le Goff (1990), Cardoso and Guimarães (2012), Benjamin (1994), among others, theoretically founded this research. From a methodological point of view, a bibliographic research was conducted based on the book "É história viva, num é história morta: narrativas do Litoral Norte" by Barbosa et al (2020). The reports were analyzed from three perspectives: oral tradition, memory, and identity. This analysis identified the presence of structures and themes that circulate other myths and stories of the Portuguese oral tradition manifested in the narratives analyzed in the research.